Is social support pre‐treatment associated with prognosis for adults with depression in primary care?. (16th February 2021) - Buckman, Joshua E. J.; Saunders, Rob; O'Driscoll, Ciaran; Cohen, Zachary D.; Stott, Joshua; Ambler, Gareth; Gilbody, Simon; Hollon, Steven D.; Kendrick, Tony; Watkins, Edward; Wiles, Nicola; Kessler, David; et al.
Abstract: Objective: Depressed patients rate social support as important for prognosis, but evidence for a prognostic effect is lacking. We aimed to test the association between social support and prognosis independent of treatment type, and the severity of depression, and other clinical features indicating a more severe illness. Methods: Individual patient data were collated from all six eligible RCTs ( n = 2858) of adults seeking treatment for depression in primary care. Participants were randomized to any treatment and completed the same baseline assessment of social support and clinical severity factors. Two‐stage random effects meta‐analyses were conducted. Results: Social support was associated with prognosis independent of randomized treatment but effects were smaller when adjusting for depressive symptoms and durations of depression and anxiety, history of antidepressant treatment, and comorbid panic disorder: percentage decrease in depressive symptoms at 3–4 months per z‐score increase in social support = −4.14(95%CI: −6.91 to −1.29). Those with a severe lack of social support had considerably worse prognoses than those with no lack of social support: increase in depressive symptoms at 3–4 months = 14.64%(4.25% to 26.06%). Conclusions: Overall, large differences in social support pre‐treatment were associated with differences in prognostic outcomes. Adding the Social Support scale to clinical assessments may be informative, but after adjusting for routinely assessed clinical prognostic factors the differences in prognosis are unlikely to be of a clinically important magnitude. Future studies might investigate more intensive treatments and more regular clinical reviews to mitigate risks of poor prognosis for those reporting a severe lack of social support.